Structural analysis of key factors in poverty alleviation for policy development in persistently impoverished provinces in Thailand - Kaewhanam, Phimlikid; Kaewhanam, Kathanyoo; Purnomo, Eko Priyo; Thongmual, Noppakun; Pongsiri, Ariya; Norrapoke, Thitima (Frontiers in Sustainability, 2025)
IntroductionPoverty remains a persistent and complex challenge in Thailand, particularly in structurally disadvantaged provinces such as Kalasin. Despite multiple national development strategies, poverty rates in Kalasin have remained consistently high over the past decade. This study addresses the structural factors influencing poverty alleviation using the Sustainable Livelihood Framework (SLF) as the theoretical lens.MethodsA longitudinal quantitative design was applied using household survey data from 2020 (n = 9,390), 2021 (n = 2,549), and 2023 (n = 1,949). The analysis focused on five forms of livelihood capital—human, physical, financial, natural, and social—and examined their changing significance over time. Structural Equation Modeling (SEM) was used to evaluate interrelationships among these capitals and their impact on poverty outcomes. Model robustness was ensured through confirmatory factor analysis (CFA), bootstrapping for bias correction, and multicollinearity diagnostics using VIF scores. Model fit was excellent across all years (RMSEA < 0.01, CFI and TLI > 0.98).ResultsFinancial capital was the dominant contributor to poverty reduction in 2020 and 2023, whereas social capital exhibited the strongest influence in 2021, reflecting the short-term benefits of community-based support during economic and social stress. Human capital maintained a moderate and stable effect across all years, while physical capital consistently showed the least contribution to poverty alleviation.Discussion and conclusionThe findings suggest that poverty alleviation in Kalasin requires an integrated policy approach that combines capability enhancement with structural responsiveness. Investments should prioritize financial capital while fostering social and human capital resilience, particularly during times of crisis. This research provides a predictive model for capital investment prioritization and contributes to policy design for sustainable poverty reduction in rural provinces.